Initialism in BBC News Online Newspapers From August 2024-March 2025: A Morphosemantic Studies - Fauziyah, Syifa Wasilatul (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The title of this research is “Initialism in BBC News Online Newspapers from August-May 2025: A Morphosemantic Studies”. The purpose of this research is to identify the form of initialism and their meanings in BBC News from August-May 2025. The method of this research is a qualitative descriptive research method. The data is collected using the observation method with a note-taking method. That method is used to describe the data in this research. The data source in this research is a News article from BBC News Website published between August 2024-May 2025. The analysis of this research was carried out using the distributional method, and the Immediate Constituent (IC) analysis technique and the expansion technique. The result of this research shows that the form of initialism is divided into two parts, those are formed from single morphemes and those are formed from combinations of single and complex morphemes. The meaning from the initialism are categorized into two meanings, they are lexical meaning (literal meaning) and contextual meaning (the meaning according to the News context).